Sacral Rachipagus Parasite: A Case Report - Rattan, Kamal Nain; Singh, Jasbir; Dalal, Poonam; Sonika, Pallavi; Rattan, Ananta (Journal of Neonatal Surgery, 2016)
We are reporting a case of sacral rachipagus parasite which was vaginally delivered as a large irregular mass attached to the sacral region by a vascular pedicle. This case was managed successfully by surgical excision of parasite.